Manufacture of sapphire ribbons with low dislocation density - Safronov, R.I.; Litvinov, L.A.; Voloshin, A.V.; Bochkov, V.F. (Functional Materials, 2016)
Uniform thermal field with the axial temperature gradient of 11.6 K/cm was formed in a cylindrical heater. There were obtained 15x85x300 mm3 sapphire ribbons with dislocation density up to 103 cm-2. The dislocation density of sapphire ribbons at the axial temperature gradient of 11.6 K/cm was found to be comparable with the one in the crystals obtained by the Czochralski and Kyropoulos methods.